Clinico-Haemato-Biochemical Changes Due To The Induced Acute Toxicity Of Chlorpyrifos In Rabbits (Oryctolagus Cuniculus) (Applied Biological Research, 2014)
Thepresentstudy was aimed to assess the acute toxic effects of chlorpyrifos  using rabbits as mammalian model. Chlorpyrifos @ 1000 mg kg-1body  weight as single oral dose (Lara-909 containing 50% chlorpyrifos) caused  marked clinical changes with 50% mortality over 24 hr. Death was  associated with muscular spasms and unconsciousness. Haematology  showed a significant increase in mean lymphocyte and basophil counts.  The blood glucose, total protein, albumin, globulin, alanine transaminase, aspartate aminotransferase, blood urea nitrogen and creatinine were not  altered significantly. It was concluded that acute chlorpyrifos toxicity was  characterized by marked clinical changes and mortality without any marked alterationsinthehaemato-biochemical indices.
Keywords: Chlorpyrifos; pathology; rabbit; toxicity